2004
DOI: 10.1021/ac049203m
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Effective Interfacial Optical Constants by Nonlinear Optical Null Ellipsometry of Chiral Films

Abstract: Nonlinear optical null ellipsometry (NONE) measurements of chiral interfaces allowed direct experimental measurement of the linear interfacial optical constants in surface second harmonic generation (SHG) measurements. Since phase information is retained in NONE measurements, the real and imaginary components of the interfacial refractive index (n and k, respectively) were uniquely obtained from the measured chiral chi((2)) tensor elements of a fluorescein-labeled bovine serum albumin film. The sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 40 publications
1
63
0
Order By: Relevance
“…Owing to its coherent nature, the emerging polarization state of SHG generated from the sample is highly dependent on both the polarization state of the incident light as well as the symmetry and orientation of the crystal (Haupert & Simpson, 2011;Boyd, 2003;Simpson et al, 2005). The polarization-dependent tensor describing SHG has up to 18 unique tensor elements defining its orientation and polarization-dependent response, compared with just three for linear optics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its coherent nature, the emerging polarization state of SHG generated from the sample is highly dependent on both the polarization state of the incident light as well as the symmetry and orientation of the crystal (Haupert & Simpson, 2011;Boyd, 2003;Simpson et al, 2005). The polarization-dependent tensor describing SHG has up to 18 unique tensor elements defining its orientation and polarization-dependent response, compared with just three for linear optics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…37,42 There are also efforts trying to show that the dielectric constant of the extremely thin monolayer is just the simple arithmetic average of the two bulk dielectric constants. 52,58,67,68 Event though the results from these approaches seemed reasonable, neglecting the anisotropic microscopic local field effect in the molecular monolayer is not likely to be physically sound.…”
Section: 64mentioning
confidence: 99%
“…51 This work is obviously not consistent with the above treatment by Shen et al It was further criticized by Roy on the inconsistency that the SAM film is considered anisotropic for SHG but assumed to be isotropic in terms of its linear optical properties. 57 Roy then outlined a macroscopic phenomenological model that treats linear and nonlinear optics of the anisotropic interface layer in a single framework, which nevertheless requires a minimum of six unknown parameters of the interfacial optical constants even for an uniaxial monolayer in SHG or SFG-VS. 57,58 Thus, Roy concluded that the conventional SHG measurement of phase and intensity may not be enough to determine the orientation of SAM. However, even though the anisotropy is undoubtedly significant on the nonlinear responses, Roy's criticism might have exaggerated the influence of the anisotropy on the linear optical property within the monolayer, which in fact only slightly modifies the reflectivity of the surface as judged from ellipsometry measurement.…”
Section: 25mentioning
confidence: 99%
See 2 more Smart Citations